Flexural performance enhancement of existing reinforced concrete beams using CFRP - Schulz, Brendan (My University, 2026)
Reinforced concrete structures often require strengthening or retrofitting due to aging structural elements, revisions to design codes, or increases in service loads. This report evaluates the use of externally bonded carbon fiber reinforced polymer (CFRP) systems for strengthening reinforced concrete beams with inadequate flexural capacity resulting from increased live loading. The design theory, step-by-step strengthening procedure, and installation methodology are presented in accordance with current design provisions. In addition, a comparative evaluation of structural performance and cost between externally bonded CFRP systems and externally bonded steel plate strengthening is conducted. Results indicate that the addition of externally bonded CFRP significantly increases the flexural capacity of the reinforced concrete section, enabling the strengthened member to satisfy updated load demands. Externally bonded steel plates also provide an effective increase in flexural strength and offer greater fabrication flexibility, as steel plates can be manufactured to specified dimensions prior to installation, whereas CFRP materials are supplied in standardized roll widths and lengths that require field cutting. Although the steel plate method demonstrated lower initial cost, CFRP strengthening offers several performance advantages, including corrosion resistance, minimal increase in dead load, high strength-to-weight ratio, and ease of installation. However, CFRP systems also present certain limitations, such as higher initial material cost, brittle failure behavior, and reduced familiarity within segments of the construction industry.
Keywords: Carbon Fiber Reinforced Polymers; Flexural perfomance enhancement